Molecular Evidence of Transmission of Influenza A/H1N1 2009 on a University Campus - Virk, Ramandeep Kaur (PLoS One, 2017)
BACKGROUND: In the recent years, the data on the molecular epidemiology of influenza viruses have expanded enormously because of the availability of cutting-edge sequencing technologies. However, much of the information is from the temperate regions with few studies from tropical regions such as South-east Asia. Despite the fact that influenza has been known to transmit rapidly within semi-closed communities, such as military camps and educational institutions, data are limited from these communities. OBJECTIVES: To determine the phylogeography of influenza viruses on a university campus, we examined the spatial distribution of influenza virus on the National University of Singapore (NUS) campus. METHODS: Consenting students from the NUS who sought medical attention at the UHC provided two nasopharyngeal swabs and demographic data. PCR was used for detection of influenza viruses. 34 full-genomes of pH1N1/09 viruses were successfully sequenced by Sanger method and concatenated using Geneious R7. Phylogenetic analysis was conducted using these 34 sequences and 1518 global sequences. Phylogeographic analysis was done using BaTS software and Association index and Fitch parsimony scores were determined. RESULTS: Integrating whole genome sequencing data with epidemiological data, we found strong evidence of influenza transmission on campus as isolates from students residing on-campus were highly similar to each other (AI, P value = 0.009; PS, P value = 0.04). There was also evidence of multiple introductions from the community. CONCLUSIONS: Such data are useful in formulating pandemic preparedness plans which can use these communities as sentinel sites for detection and monitoring of emerging respiratory viral infections.